Membangun Ketertarikan Pada Bidang Matematika Terhadap Seorang Anak Di Salah Satu Lembaga Kesejahteraan Sosial Anak - Intan Purnama Adri; Randa Putra Kasea Sinaga (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
This writing started with a child who had problems related to mathematics, and here I am building his interest in mathematics so that the US is interested in mathematics. We both know that in this life, we are very close to mathematics. There are many competitions that always involve mathematics. From here we should already know that mathematics is very important in our lives. The US problem itself was related to mathematics which started when the teacher scolded the US for not being able to answer the questions given to the US. And here we also know that the role of a teacher is very important in influencing a child's interest. The intervention program that is suitable for use in this problem is the micro intervention by Skidmore in Adi, 2013, a case work consisting of stages, namely the Engagement, Intake, Contract, Assessment, Program Planning, Intervention, Evaluation, and Termination Stages. By using the skidmore method, the authors more easily solve client problems. Not only that, the approach taken by the author to children in institutions is also the right choice, and can be a reference for people in carrying out solutions and approaches like the author did. The author who helped the US in its problems hopes that the US will continue to love mathematics and can help children in institutions in learning mathematics.